2013
DOI: 10.1016/j.chembiol.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Burkholderia pseudomallei Acute Phase Antigen BPSL2765 for Structure-Based Epitope Discovery/Design in Structural Vaccinology

Abstract: We solved the crystal structure of Burkholderia pseudomallei acute phase antigen BPSL2765 in the context of a structural vaccinology study, in the area of melioidosis vaccine development. Based on the structure, we applied a recently developed method for epitope design that combines computational epitope predictions with in vitro mapping experiments and successfully identified a consensus sequence within the antigen that, when engineered as a synthetic peptide, was selectively immunorecognized to the same exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(119 citation statements)
references
References 38 publications
3
116
0
Order By: Relevance
“…This result is consistent with our previous studies, which showed that levels of antibody against BPSL2765 (OmpA protein) were 10-fold higher in individuals with melioidosis (12). A recent study showed that the levels of specific antibodies that increased against the BPSL2765 peptide effectively enhanced phagocytosis and ROS production in an opsonization and killing assay using B. pseudomallei (16). This result suggests that the levels of antibodies are likely to play an important role in the response to B. pseudomallei infection.…”
Section: Discussionsupporting
confidence: 82%
“…This result is consistent with our previous studies, which showed that levels of antibody against BPSL2765 (OmpA protein) were 10-fold higher in individuals with melioidosis (12). A recent study showed that the levels of specific antibodies that increased against the BPSL2765 peptide effectively enhanced phagocytosis and ROS production in an opsonization and killing assay using B. pseudomallei (16). This result suggests that the levels of antibodies are likely to play an important role in the response to B. pseudomallei infection.…”
Section: Discussionsupporting
confidence: 82%
“…Linear epitopes sometimes have an elevated level of antibody reactivity than the parental antigen. As for example, two acute phase antigens (BPSL 2765 and OppA) of Burkholderia pseudomallei (46,47). An antigen contains several epitopes, some of which are specific to the parental organism.…”
Section: Discussionmentioning
confidence: 99%
“…17,40,41 Lipopolysaccharide removal was carried out by incubating each purified protein sample overnight at 4°, in a Pierce High Capacity Endotoxin Removal Spin Column (Thermo Fisher Scientific, MA), according to the manufacturer's instructions. 17,40,41 Lipopolysaccharide removal was carried out by incubating each purified protein sample overnight at 4°, in a Pierce High Capacity Endotoxin Removal Spin Column (Thermo Fisher Scientific, MA), according to the manufacturer's instructions.…”
Section: Recombinant Antigen Productionmentioning
confidence: 99%